CADAR PERSPEKTIF MUFASIR: Interpretasi Mufasir Salaf Hingga Muta’akhirin Terhadap Ayat 59 Surah al-Ahzab - Haidir Rahman (UIN Siber Syekh Nurjati Cirebon, 2017)
The veil polemic has recently become a hot topic for discussion. Veiled behavior is seen as a symbol of radical Islamic understanding. This assumption raises a negative response from some parties who counter the veiled behavior. This negative response on the one hand has injured individual freedom in carrying out the teachings of Islam. This paper tries to examine veiled behavior from the point of view of interpretive science. In this study the opinions of the commentators will be revealed since the Salaf era until the Muta'akhirin era. How they view the activity of covering the face with a veil for Muslim women. The focus of the study will be directed at the interpretation of verse 59 surah al-Ahzab as the legal basis for the rule of dress for Muslim women. The findings in this study show that the majority of commentators interpret verse 59 surah al-Ahzab as a command to cover faces for Muslim women. Their interpretation shows that veiled behavior is a behavior that is positive and not part of a radical understanding feature.